POLYSACCHARIDE FROM THE ROOTS OF POLYGONUM EQUISETIFORME SIBTH. & SM.: ISOLATION, CHEMICAL COMPOSITION, - TAGHREED A. IBRAHIM; ATEF A. EL-HELA (International Journal of Pharma and Bio Sciences, 2012)
A water-soluble polysaccharide (PEP) was isolated and purified from the aqueous extract of Polygonum equisetiforme Sibth. & Sm. roots. Structural features of PEP were investigated by a combination of instrumental and chemical analyses, including acid hydrolysis, methylation analysis, IR, GPC, HPLC and GC/MS. The results indicated that PEP has a backbone of (1→4)-linked glucose residues, which occasionally branches at O-6. The branches are mainly composed of (1→4)-linked rhamnose, (1→6)-linked glucose, (1→6)-linked galactose and (1→3)-linked mannose and terminated with arabinose and rhamnose residues. PEP exhibited high ABTS, DPPH, OH free radicals scavenging activities compared to the ascorbic acid reference control. The in vitro cytotoxicity of PEP was dose-dependent with IC50 values of 14.67 µg/mL and 22.34 µg/mL against colon and breast cancer cell lines, respectively. These results suggest that PEP may be an effective natural antioxidant compound, with little antitumor activity.